Sytuacja socjolingwistyczna mniejszości bułgarskiej na południowo‑wschodniej Ukrainie - Krasowska, Helena (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2023)
The subject of the research is the Bulgarian minority living in the south‑eastern areas of Ukraine. The aim of the article is to present the sociolinguistic situation of this minority. Particular attention was paid to the use of the Bulgarian language in the family and neighborhood sphere. The determinants that maintain or lead to the disappearance of the Bulgarian culture and language in the Zaporozhye region are indicated. Field research among the Bulgarian minority was conducted in 2013–2022 on the margin of research that was conducted among the Polish minority in this region. The leaders emphasized that no one at home uses the Bulgarian language, although some people remember how their grandparents once used the dialectal variety of the Bulgarian language. In the neighborhood environment, no one speaks Bulgarian in this area either. No one speaks Bulgarian in the families, and Bulgarian is not spoken in the neighborhood either. Living in a linguistically different environment was conducive to rapid assimilation to most of the Russian language. In the family sphere and intergenerational transmission, only Russian is present. The research results also make it possible to indicate the reasons for the loss of linguistic continuity among the Bulgarian minority in the Zaporizhia region. Currently, representatives of the Bulgarian minority are learning Ukrainian.